Thermophilic biohydrogen production for commercial application: the whole picture. (29th October 2015) - Gupta, Niharika; Pal, Mili; Sachdeva, Meenu; Yadav, Mahaveer; Tiwari, Archana
Summary: Hydrogen is a promising alternative to fossil fuel for a source of clean energy. Thermophilic biohydrogen production is beneficial for obtaining high H2 production yield. This review recapitulates the basic metabolic pathways in bacteria for hydrogen production and the enzymes involved in various thermophilic hydrogen producing pathways in microorganisms. It also focuses on the current status of thermophilic biohydrogen production through fermentation of commercially viable substrates, such as agricultural residues. The use of metabolic engineering to attain certain physiological desirable characteristics in H2 ‐producing microorganisms, culture conditions, and types of bioreactors to be used are reviewed. Major obstacles in industrial production of biohydrogen like low volumetric hydrogen production and its environmental impact are identified. The review has further identified current limitations in the commercial thermophilic hydrogen production and suggested methods like the use of heat exchangers and effluent recirculation to reduce the production cost. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : It covers various thermophilic hydrogen producing microorganisms, the enzymes involved in their metabolic pathways and various metabolic engineering that can be applied on microbes to enhance hydrogen productivity. Types of bioreactors and culture conditions that can improve biohydrogen production.